2011
DOI: 10.1007/s12160-011-9303-z
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Control Mediates the Prospective Impact of Relationship Quality in the Year After Colorectal Cancer Diagnosis

Abstract: Collective control mediates the relationship between family relationship quality and satisfaction with life, suggesting the need for interventions to enhance relationship quality and perceived control among newly diagnosed cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 60 publications
(81 reference statements)
0
15
0
1
Order By: Relevance
“…Our previous studies have consistently found interpersonal adaptive mechanisms for Chinese people with cancer. For instance, relationship quality and collective (i.e., in collaboration with close social partners) instead of personal sense of control over cancer predicted lower anxiety and depressive symptoms among these people (Hou, 2010;Hou & Lam, 2014;Hou & Wan, 2012). On the other hand, the association between emotion-focused positive rumination and depressive symptoms in the mediation model was insignificant despite their significant bivariate correlation (r = À.18, p < .01).…”
Section: Discussionmentioning
confidence: 88%
“…Our previous studies have consistently found interpersonal adaptive mechanisms for Chinese people with cancer. For instance, relationship quality and collective (i.e., in collaboration with close social partners) instead of personal sense of control over cancer predicted lower anxiety and depressive symptoms among these people (Hou, 2010;Hou & Lam, 2014;Hou & Wan, 2012). On the other hand, the association between emotion-focused positive rumination and depressive symptoms in the mediation model was insignificant despite their significant bivariate correlation (r = À.18, p < .01).…”
Section: Discussionmentioning
confidence: 88%
“…Worse mental health outcomes in CRC patients have been associated with younger age, lower socioeconomic status, increased perceptions of illness-related benefits, and poorer physical health outcomes (e.g., greater physical symptom distress and medical comorbidities, bowel dysfunction) [2,514]. Conversely, greater social support and, among Chinese CRC patients, a greater sense of personal control and collective control (i.e., control over cancer-related problems in collaboration with loved ones) have been associated with better mental health outcomes during the acute CRC survivorship period [7,10,12]. …”
Section: Introductionmentioning
confidence: 99%
“…It was reported that social context represented a powerful resource in studying the impact of perceived control on adjusting to chronic illnesses (Hou & Wan, 2012). Previous data showed that a supportive social network is essential for the integration of disease information, nutrition support and involvement in symptom management, which results in positive psychological outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, the patients with lower perceived control did not believe they had the ability to influence the cancer course or their symptom distress (Kidd et al, 2009). It was reported that perceived control included the cancer experience and treatment efficacy for coping with cancer (Hou & Wan, 2012). Perceptions of intrapersonal control were associated with better coping, adjustment in chronic disease and physical outcomes (Kidd et al, 2009;Mystakidou, Tsilika, Parpa, & Galanos, 2015).…”
Section: Introductionmentioning
confidence: 99%